Reproductive performance, pre-weaning growth rate and pre-weaning lamb mortality of Djallonke sheep in Ghana - Tuah, A.K; Baah, J. (Springer, 1985)
Production records for a flock of Djallonke sheep kept in the forest belt of Ghana were analysed to determine the effects of some environmental factors on the performance of the breed between 1969 to 1979. The mean ages at first conception and first lambing and the mean lambing interval were 498, 638 and 264 days respectively. The overall birth and age of dam had significant (P